Invenções de um corpo na prática teatral de atores com bonecos - Adriana Maria Cruz dos Santos (2019)
We aim with this thesis to study the composition of a fictional body made in the theatrical relationship between puppet and actor/performer, or, better said, in a mode of theater with puppets. It involves the study of creation procedures and performance under the light of the singularities of the work developed by the actors/performers – which were interviewed on/for the making of this thesis. The writing process followed the conceptualization of the body in theater practices taking in account the procedures of interaction between the two participants in the action – the puppet and the actor/performer. These procedures, in the way we approach them here, are based on the creative work of the actor/performer with the puppet. Thus we point out to a possibility of an articulated connection that is established in stages: first the contact, then the connection and lastly the fusion of the body of the actor/performer with the puppet, and, as an effect of such fusion, the invention of a substance-body that embodies the character itself. Taking in consideration that in the field of investigation of creative procedures the puppet is a character and the actor/performer a “facilitator” of its presence, our work approaches the composition of this fictional body related to this condition of character attached to the puppet and also studies the actor/performer as a decisive co-participant in the scene. Our research brings to the surface important reflections on the actor/performer’s work and also traces the construction of the scene’s poetics in the perspective of the actors.